ANALISIS NILAI TAMBAH PENGOLAHAN PALA KEMASAN BASAH DAN KERING DI KECAMATAN TAPAKTUAN KABUPATEN ACEH SELATAN - Mujiburrahmad Mujiburrahmad (Jurnal Bisnis Tani, 2019)
Added value is the value added of a commodity because it undergoes a process of processing, transporting, and or storing in a production. In the process of processing added value can be defined as the difference between the value of the product and the cost of raw materials and other inputs, not including labor. Processing and changing the shape, taste, aroma and packaging of nutmeg meat products will produce new added value which can affect higher selling prices. The purpose of this study is to determine whether the processing of wet and dry nutmeg can provide added value and any factors that influence the added value of wet and dry nutmeg processing in Tapaktuan sub-district, South Aceh district. The analytical method in this study is the Hayami method to calculate added value and multiple linear regression analysis methods for factors. Based on the results of the study showed that dry packaging provides added value of Rp.8,135,775 and wet packaging provides added value of Rp.54,859,446. As for the factors that provide added value for dry packaging (nutmeg cake), namely the factor of the amount of production with a significant 0.000, labor with a significance of 0.021, and the amount of material with a significance of 0.000. And for wet packaging (nutmeg syrup) that is a labor factor with a significance of 0.007.